Asset Correlation and the Optimal Portfolio Size Determination – Case of Nifty 50 and NASDAQ 100 Indices - Joshi, Himanshu (Indian Journal of Research in Capital Markets, 2022)
Portfolio diversification benefits and optimum portfolio size depend on the internal correlation structure of the market. Investors require a small number of assets to get the maximum diversification benefit in a highly correlated market, however, such a market offers relatively lesser diversification opportunities. In the present study, the correlation for stock returns in India and the US was calculated to determine the optimal size of portfolios in the respective markets. Returns for all stocks indexed in NIFTY 50 and NASDAQ 100 were considered for calculating average correlations for Indian and U.S. markets between 2017 and 2019. The results showed higher correlations for the NASDAQ 100 in comparison to Nifty 50, indicating relatively better diversification opportunities provided by the Indian market as compared to the U.S. However, lower correlations for Nifty 50 required a larger number of assets to be included in the portfolio to diversify the unsystematic risk. Correlations between Nifty-50 and Nasdaq-100 indices for the past three years 2017–19 were also calculated. The results showed a relatively low correlation between the two indices, which is good for international diversification opportunities. In addition, the present study established a relationship of correlation structure between the two indices and foreign capital inflows in India for the respective years. This study also captured the cross-country returns and risks for the Indian and the U.S market.